Girolamo Fabrici d’Acquapendente’s “nasogastric tube”. Strategies for artificial nutrition between the XVI and XVII centuries - Zampetti, Paolo; Cozza, Andrea; Rippa Bonati, Maurizio (Medicina Historica, 2020)
The contribution focuses on the idea proposed by Girolamo Fabrici d’Acquapendente to use a nasogastric tube to feed patients who are unable to open their mouths and independently take food and drinks.